Nivel de conocimiento en residuos sólidos en pobladores del asentamiento humano "Silfo Alvan" de Villa Punchana. Distrito de Punchana. 2022 - Valdivia Bardales, Lidia Maria (2022)
The research evaluated the level of knowledge in solid waste in the inhabitants of the Silfo Alvan human settlement of the Punchana district in the year 2022. The research, due to its approach, was quantitative, prospective, simple descriptive and nonexperimental research design. The target population of the study consisted of all the inhabitants of the AA.HH. Silfo Alvan in the year 2022. The sample also consisted of 65 residents, who were present at the time of the application of the data collection instrument, using the survey with a questionnaire of ten questions, the same one that passed the validity tests. (4 experts) and reliability. The data obtained are expressed in a Basic Data Matrix (MBD) being processed with the statistical package SPSS version La 25. The main conclusions were that there is a general lack of knowledge about basic concepts about solid waste in the inhabitants of AA.HH Silfo Alvan 2022. The level of knowledge in general about solid waste was predominantly low with 56.9%, 30.8% had a regular level and only 12.3% had a high level of knowledge. In the level of knowledge about solid waste according to sex there are a predominance of the low level of knowledge in both sexes with 48.7% in the male sex and 68.7% in the female sex, being much more accentuated still in the female sex in relation to the regular and high level. The level of knowledge in solid waste according to the level of instruction, the level of low knowledge predominated in the degrees of instruction of the resident, with 55.6%. 56.3% and 62.5% respectively. This predominance is much more accentuated in the degree of complete secondary education and that according to the trend it is observed that the higher the level of instruction in the lower population is the level of knowledge in solid waste. The level of knowledge in solid waste in all age groups with the exception of 18 to 29 years predominates the low level of knowledge.